Evaluasi Kinerja Koperasi Perkebunan Sebagai Mitra Perkebunan Kelapa Sawit PT. Sepanjang Intisurya Mulia - Komariyati, Fardy Akhyarsyah, Ani Muani, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2017)
The research aims to collect the information of the existing partnership model PT. Sepanjang Intisurya Mulia and to asses the performance of the partnership scheme and capacity building cooperative Sawit Trimulya Lestari Plantation in the village Pangkalan Teluk Cooperative Capacity Assessment (CCA)analysis method with a sample of 30 people taken randomly. The research results were showed the cooperative plantations Sawit Trimulya Lestari have 406 members with 812 ha land areahas good criteria. The assessment of performancemeasured through five aspects: a) Institutional have an excellent criteria(19.43%) and a good criteria (68.74%). b) Cooperative Business have an excellent criteria (2.04%) and a good criteria (95.92%). c) Services have an excellent criteria (20%) and a good criteria (80%). d) Members Participation have a good criteria (83.33%). e) Job Network have an excellent criteria (33.33%) and a good criteria (66.67%). Institutional aspects (11.83%), cooperative effort (2.04%) and participation of members (16.67%), are have a sufficient criteria that need to be improved the performance only in certain aspects and at the proper time. Excellent criteria indicate thatthe performance need to be maintained at the level of effectiveness in its application and good criteria indicate that in some aspects and indicators its necessary to optimize the performance in its application.The variables that should be improved is the development of human resources and infrastructure improvement.Keywords : Cooperative Performance, Cooperative Capacity Assessment, PT. Sepanjang Intisurya Mulia